Clinical profile of seizure disorder in hospitalized patients - Dhadke, Vithal N.; Dhadke, Shubhangi V.; Dawar, Ajay (International Journal of Advances in Medicine, 2017)
Background: Hughling Jackson in 1870 described first “seizures as intermittent derangement of central nervous system and abnormal and excessive discharge of central nervous tissue on muscles” and the same was refined further. Average incidence rate for epilepsy is 0.3 - 0.5% in patients. Methods: A total of 100 patients admitted with sign and symptoms suggestive of seizure disorder in tertiary care hospital during the period of 1st December 2012 to 31st July 2014. A detailed clinical history, examination and investigation with following patients were included in study; (1) age of the patients above 13 years; (2) patient present with history of seizure the cross sectional observational study was carried out at Dr. V. M. Government Medical College, Solapur, Maharashtra, India. Results: Generalized tonic clonic were the commonest type seen in 69 patients (69%) and cerebrovascular disease because seen in 25 patients (25%) is the second most common cause. Conclusions: (1) Ring enhancing lesion were seen in 15% patients, among most common was tuberculoma that is seen in 10 patients and neurocysticercosis was seen in 5 patients; (2) cerebral tumour was seen in 4 patients; (3) EEG was abnormal in 31% cases of seizure and most common EEG abnormality was focal slow waves and (4) CT scan abnormality was seen in 47 cases (47%).